Analisis Gerombol Pautan Ward Kabupaten/Kota di Provinsi Jawa Timur Berdasarkan Indikator Kesejahteraan Rakyat - annida marsa salsabila; Mohammad Masjkur; Indahwati (Xplore: Journal of Statistics, 2022)
The main goal in the development of a country is to improve the welfare ofthepeople. One of the causes of the problems of people's welfare in Indonesia is that thedevelopment carried out by the government is not carried out evenly and not on target,not least in East Java Province. to group and look at the characteristics of 38regencies/cities in East Java Province based on people's welfare indicators sothat thegovernment in making policies can be evenly distributed and on target. Thisstudy useshierarchical cluster analysis. The data used is the welfare indicator data for 38districts/cities of East Java Province in 2019. The hierarchical cluster analysismethodused is the Ward method. The results of the study using dendogram cuts and the ratioof standard deviations within clusters and standard deviations betweenclusters showedthat districts/cities in East Java province could be divided into six clusters. In eachcluster, the characteristics are seen using the average value of eachvariable. Areas withvery good development are in cluster six and areas that requiremore development inmany aspects are in cluster five.